Review of the Diversity, Ecology, and Conservation of Elasmobranchs in the Azores Region, Mid-North Atlantic - Das, Diya; Afonso, Pedro (Frontiers in Marine Science, 2017)
A vulnerable species group, such as the elasmobranchs, in a data-deficient context presents a complicated management problem. Evidence suggests that the Azores islands, a remote archipelago on the Mid-Atlantic Ridge, serve essential functions in the life-history of species across taxa. The diversity of marine resources within its EEZ are exploited by local to international fleets, and the full extent of fishing pressure can often be underestimated. Although sharks and rays appear to be of minor importance in the fishery, the possibilities of illegal, unreported and unregulated fishing raises concerns about these threatened species. However, this group has failed to attract management attention, visible in the lack of regional studies focused on biodiversity, ecology or threats of elasmobranchs. Our work attempts to review and update the information on elasmobranchs of the Azores and identify potential threats, mainly by the local fisheries. We aim to highlight knowledge gaps that require further research and conservation actions. We 1) update the annotated checklist of elasmobranch species, 2) compare species distribution across a biogeographically similar section of the North Atlantic, and 3) analyze the interaction of elasmobranch species with local fisheries. We confirm 61 chondrichthyan species for the Azores (39 sharks, 17 rays and 5 chimaeras), adding 19 species to the previous annotated checklist of 1997. The Azores elasmobranch species assemblage most resembles Madeira, the neighboring Macaronesian archipelago. Biogeographic affinities between the chosen regions of the North Atlantic are reflected in the taxonomic structure of families. Although underestimated in the local fisheries, elasmobranchs constitute a regular but highly variable portion of total landings. Misreporting and misidentification is perhaps the greatest concern in the local fisheries records, further aggravated by few existing catch regulations for elasmobranchs. Local knowledge indicates that the Azores serves as essential habitat for at least a few species in coastal areas and shallow seamounts, and potentially so for a number of deep-sea elasmobranchs. The intersection of fishery threats and local essential habitat functions around the archipelago warrants greater research effort and studies.